HUBUNGAN ANTARA GROWTH MINDSET DENGAN PRESTASI AKADEMIK SISWA SDN 1 KEMBANG SARI - Mustaqimah, Annisa; Muspita, Zalia; Ade Maharani, Aprilia; Wanda Citria, Baiq; Putri Murdiani, Hurul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Elementary school students' academic achievement is often viewed merely as a function of cognitive ability, yet students' beliefs about the nature of their own abilities also shape how they respond to learning difficulties. This study aimed to determine the relationship between growth mindset and academic achievement among students at SDN 1 Kembang Sari. A quantitative correlational design was employed. The sample consisted of all 33 students in grades IV, V, and VI of SDN 1 Kembang Sari, selected through total sampling. Growth mindset was measured using a Likert scale adapted from Dweck's framework, while academic achievement was obtained from the documentation of students' current-semester average report card scores. Data were analyzed through normality testing, Pearson Product Moment correlation, and simple linear regression. The normality test showed that the data were normally distributed. The correlation test revealed a positive and significant relationship between growth mindset and academic achievement, with a correlation coefficient of 0.521 and a significance value of 0.003 (p < 0.05), categorized as moderate. The regression analysis showed that growth mindset accounted for 27.1% of the variance in students' academic achievement, while the remaining 72.9% was explained by other factors outside this study. These findings indicate that the higher students' growth mindset, the higher their tendency toward academic achievement. This study recommends that elementary school teachers regularly provide feedback that emphasizes learning process and effort in order to foster a growth mindset from an early age.